2021
DOI: 10.1021/acsanm.1c02884
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanopolyhedron-Based Superlattice Sheets as Flexible Surface-Enhanced Raman Scattering Sensors for Detection of 4-Aminothiophenol

Abstract: The self-assembly of plasmonic building blocks into superlattices has emerged as a promising route to fabricate metamaterials with customizable nanoscale architecture and collective properties. However, self-assembly of such plasmonic superlattice has proven challenging, owing to the low packing fraction, complex interparticle forces, and local heterogeneity. Besides, the conventional assembly of small nanoparticles usually exhibits localized defects and uncontrollable electromagnetic field distribution, limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…The value was larger compared to others reported elsewhere because a silica layer exists between metallic surface and p-ATP. [29][30][31] However, the silica layer enables SERS measurements without chemical transformations, which would be applicable to unknown samples in practical uses.…”
Section: Resultsmentioning
confidence: 99%
“…The value was larger compared to others reported elsewhere because a silica layer exists between metallic surface and p-ATP. [29][30][31] However, the silica layer enables SERS measurements without chemical transformations, which would be applicable to unknown samples in practical uses.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the optical properties of plasmonic supercrystals (such as Au NPSCs) can be designed by combined control over the nanoscale (interparticle distance, i.e., volume fraction of plasmonic nanoparticles) and mesoscale structures (supercrystal habit and size). The tailored optical properties of plasmonic NPSCs would allow us to manipulate lights, providing new opportunities in potential applications including solar energy harvesting, optical electronics, molecular sensing, and photocatalysis …”
Section: Resultsmentioning
confidence: 99%
“…The electromagnetic field can be controlled by the combination of metasurface design and SPs. Therefore, the method of combining LSPR and SERS based on metal nanostructure will have broad prospects [9]. By designing the nanostructure, the optical response can be optimized effectively, and thus favorable sensing sensitivity can be achieved [10,11].…”
Section: Introductionmentioning
confidence: 99%